К вопросу таможенной политики Республики Беларусь - Макарова, Е. В. (БНТУ, 2020)
This article discusses the concept of the customs policy of the Republic of Belarus. The main tasks of customs policy, its goals and functions are considered. Favorable conditions for the economic policy of the state are also considered.